Exploration of the Impact of Social Media on Children's Learning Mechanisms - Emily Smith; Nesti Anggraini Santoso; Musyfiq amrullah Ar Romdhoni; Nur Azizah; Eka Dian Astuti (Pandawan Sejahtera Indonesia, 2024)
In this study, we investigated the complex relationship between social media and children's learning processes during childhood. Although research on student responses to e-learning platforms in pediatric contexts continues to grow, there remains significant confusion regarding the factors that shape acceptance of e-learning conducted via social media applications. To fill this gap, our study analyzes the influence of social media practices, especially in the context of knowledge sharing, features, motivation, and social media use, on how children respond to e-learning systems. In this effort, we expanded the existing Technology Acceptance Model (MPT) to accommodate these factors. We also conducted a comprehensive survey involving 100 children and their parents as research participants. They participate by answering questionnaires, which provide valuable empirical data. Using the powerful SMART-PLS analysis technique, we perform a careful analysis of the extended model. The results of our empirical data analysis confirm that social media practices have a significant positive impact on Perceived Effectiveness (PU) and Perceived Ease of Use (PEOU) in the context of children's learning mechanisms. Our main findings emphasize the central role of PU and PEOU in influencing how children receive e-learning systems. In other words, this paper highlights the potential changes that social media practices can bring about in shaping the acceptance of e-learning systems, while contributing to our understanding of the interactions between social media, MPT factors, and e-learning acceptance in the context of educational programs children.